Tren Prevalensi dan Disability-Adjusted Life Years (DALY) Diabetes Melitus di Indonesia: Analisis Data GBD 2021–2023 - Sandi Nur Fathana Laliasa; Yaltafit Abror Jeem; Vita Widyasari (Jurnal Kesehatan Amanah, 2026)
This study analyzed trends in the prevalence, incidence, and burden of Diabetes Mellitus in Indonesia from 2021 to 2023 and identified geographic disparities across provinces. A descriptive-analytical approach was applied using standardized Global Burden of Disease data to assess changes in prevalence and disease impact measured by Disability-Adjusted Life Years. The results indicated a consistent increase in the prevalence of Diabetes Mellitus over the study period, with substantial variation between provinces. Regions with higher prevalence experienced a greater disease burden compared to low-prevalence areas, although a gradual decline in Disability-Adjusted Life Years was observed. These findings suggested improvements in disease management and complication prevention, while inequalities in health service access and socioeconomic conditions continued to influence regional differences. This study concluded that Diabetes Mellitus remained a major public health challenge in Indonesia and required more targeted, region-specific control policies emphasizing prevention, early detection, and strengthening of primary health care services to reduce disparities and future disease burden.